2019
DOI: 10.1007/s41649-019-00084-4
|View full text |Cite
|
Sign up to set email alerts
|

People-centred Universal Health Coverage in the Asia-Pacific

Abstract: Universal health coverage (UHC), variedly construed, is not a new concept. In international politics, it emerged as a global health agenda in the 1920s, became marginalised by the 1950s, but re-emerged as BHealth for All^in the Declaration of Alma-Ata in 1978 (Gorsky and Sirrs 2018). The commitment then was to advance primary health care by linking health with community action, multilateral collaboration and social justice. Since then, health and health-related campaigns such as, for example, the Millennium De… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…We welcomed the new year with an international research seminar that sought to consider the ethical implications of the Astana Declaration on endeavours directed at Universal Health Coverage (UHC) in a number of Asia-Pacific countries. Some of the works presented in this seminar have been published in the March instalment of the journal, which had people-centeredness in UHC as its central theme (Ho and Caals 2019). In the second instalment of the journal for the year, we published papers that not only reached back to earlier discussions on ethical deliberations around biodiversity (Lajaunie and Morand 2018) but also forward to ethical approaches in the evaluation of the Big Data phenomena in health research.…”
mentioning
confidence: 89%
“…We welcomed the new year with an international research seminar that sought to consider the ethical implications of the Astana Declaration on endeavours directed at Universal Health Coverage (UHC) in a number of Asia-Pacific countries. Some of the works presented in this seminar have been published in the March instalment of the journal, which had people-centeredness in UHC as its central theme (Ho and Caals 2019). In the second instalment of the journal for the year, we published papers that not only reached back to earlier discussions on ethical deliberations around biodiversity (Lajaunie and Morand 2018) but also forward to ethical approaches in the evaluation of the Big Data phenomena in health research.…”
mentioning
confidence: 89%
“…Furthermore, the Pakistan study also added that 57% of the medical and dental residents did not know the code of ethics of the Pakistan Medical and Dental Council, and Studies conducted in India among physicians, medical residents, and nurses reported that the knowledge of ethics ranged from 34.8% to 59% [ 21 , 22 , 24 , 25 ]. These findings indicate the necessity of improved educational methods of medical ethics and warrant regulations to implement the practice of bioethics in the healthcare delivery system in India and other Asian countries [ 46 48 ] as well. The vast difference in the knowledge level between these studies with our study could be attributed firstly to the large sample size in this study, secondly, this study included a varied range of professionals unlike the other studies and the construct of the KAP questions varied as well.…”
Section: Discussionmentioning
confidence: 99%
“…Factors that prevent women from receiving or seeking health care during pregnancy and childbirth include inadequate services, poverty, distance, lack of information, and cultural practices [7] . Underutilization of health services is one factor contributing to high maternal mortality rates, for example, 81% of births take place at home, many without skilled health providers [8] .…”
Section: Introductionmentioning
confidence: 99%